A Consular Report from Chernivtsi to the Romanian Foreign Minister about the Political Situation in the Duchy of Bukovina (1914) - Vlad Gafiţa (Codrul Cosminului, 2010)
The document that was found in the Archives of the Foreign Ministry is a Report of the Romanian Consulate in Bukovina and Galicia. It presents the political struggles of the Romanian parties (Democratic Party, National Party and the Independent Center Party) in the months preceding the onset of the First World War. The Austrian authorities diligently pursued Romanians, suspecting them of treason, irredentism, and lack of loyalty to the Habsburg dynasty.